Structural‑phase composition of a gas‑thermal coating of Fe‑Cr‑Ni‑Al pseudo alloy subjected to annealing - М. A. Belotserkovsky; V. A. Kukareko; Yu. S. Korobov; E. V. Astrashab; I. I. Grigorchik (Литьë и металлургия, 2021)
The structural‑phase state of the gas‑thermal coating made of Fe‑Cr‑Ni‑Al pseudo‑alloy in the initial state, as well as after annealing in the temperature range 550–650 °C for 20–60 minutes, has been investigated. It has been established that the phase composition of the Fe‑Cr‑Ni‑Al pseudo‑alloy in the initial state includes mainly Al and α‑Fe, and its porosity does not exceed 3–5 vol.%. Annealing of a thermal spray coating from a pseudo‑alloy at temperatures of 550–650˚C for 20–60 minutes leads to the release of iron‑aluminum intermetallic compounds Fe3Al, Al13Fe4 and Al5Fe2, an increase in hardness and porosity.